Design Of Non-Contact Human Body Temperature Detection Based On Internet Of Things (Iot) To Open The Door Automatically - Karsono, Kundang; Irawan, Bambang; Sulistio, Alip (International Journal of Science, Technology & Management, 2022)
Covid-19 has hit Indonesia since March 2020; as a policymaker, the government has imposed new regulations so that everyone can leave the house and do work without worrying about being exposed to the Covid-19 virus. Measurement of body temperature is the fundamental way to determine the condition of body temperature. However, the problem is that when a thermometer is used to check the temperature of the human body, it is still carried out in direct physical contact between humans so that the risk of transmission of the covid-19 virus can occur. Based on these problems, a thermometer was made, which can be used to check human body temperature without making physical contact. Using the prototype method and system design with UML diagrams, the temperature sensor GY-906 MLX90614 (Temperature detection sensor) was used to build a prototype non-contact human body temperature detection monitoring system based on the Internet of Things (IoT) to open doors automatically.). body), LCD (Liquid Crystal Display) displays the results of the human body temperature, servo motor as an action system in the form of a sliding door controller, ESP8266 Wifi Module, which is used as a microcontroller that processes sensor data and sends sensors through a wireless network. The data sent by the ESP8266 Wifi Module can be monitored via a Web application.